Can the Boston Carpal Tunnel Syndrome Questionnaire Be Used as a Screening Tool Among a Potentially High-Risk Population in Singapore? - Sirisena, Dinesh; Lim, Ivan; Sim, Shauna; Tong, Pei-Yein; Rajaratnam, Vaikunthan (Journal of Hand and Microsurgery, 2020)
Introduction Carpal tunnel syndrome (CTS) causes significant morbidity with delayed diagnosis or management. The Boston Carpal Tunnel Questionnaire (BCTQ) is validated for monitoring CTS following diagnosis; however, it has not been trialed in a screening capacity. The study aimed to determine whether it can be utilized when screening a focused population in Singapore.Materials and Methods A single-center survey-based study was undertaken prospectively to identify whether positive symptoms could be identified among nursing and administrative staff.Results A total of 605 staff responded. Positive symptoms were identified in 317 (52.4%) of participants and 23 (3.8%) reported them to be severe. Functional limitations were detected in 157 (26.0%) of participants with 5 (0.8%) reporting these as severe. Positive symptoms (84.9%) and functional limitations (81.5%) were more prevalent among nursing staff. Cronbach’s α scores (0.896 for symptoms and 0.84 for functional limitations) suggested good reliability in matching symptoms and functional limitations.Conclusion The BCTQ can potentially be implemented as a screening tool for CTS among those without a prior diagnosis. It has a greater depth of questioning with symptomatic and functional limitations considered, and in situations where a formal diagnosis is subsequently made, the same tool can be subsequently used for progression tracking pre- and post-treatment.Level of Evidence  This is a Level II study.
Keywords: carpal tunnel syndrome; Boston Carpal Tunnel Questionnaire; median nerve; peripheral nervous system disorders; mass screening